Color and meaning in ancient Mesopotamia: the case of Egyptian Blue - Thavapalan, Shiyanthi (Zeitschrift für Assyriologie und vorderasiatische Archäologie, 2016)
Despite its ubiquitous presence and obvious cultural significance in Mesopotamian art and architecture, the Akkadian language never developed a specific term for the color ‘blue.’ This article seeks to explain this omission and the Akkadian color system in light of ethno-linguistic data collected in the University of California-based World Color Survey project and the physical evidence for blue pigments and colorants. Special attention is paid to the results of multispectral-imaging analysis conducted on Yale University’s Assyrian relief sculpture from Nimrud. This investigation has revealed the use of Egyptian blue pigment in unexpected and hitherto unknown contexts in Assyrian architectural design.